The compressible laminar boundary layer with foreign gas injection - Craven, A. H. (College of Aeronautics, 1962)
The equations of the steady compressible two-dimensional laminar boundary layer with foreign gas injection through a porous wall are solved, using an extended form of Lighthill's approximate method, for arbitrary main stream pressure gradient, wall temperature and injection velocity. The wall shear stress and heat transfer rate are obtained in the form of equations suitable for iteration. It is shown that substantial reductions in skin friction and heat transfer rate can be obtained by the injection of a light gas instead of air.